1T MoS2 growth from exfoliated MoS2 nucleation as high rate anode for sodium storage. (22nd October 2021) - Xu, Zhanwei; Liu, Xinyue; Yao, Kai; Ren, Yuchuan; Li, Jiayin; Shen, Xuetao; Li, Zhi
Abstract: Recently, metallic 1T MoS2 has been investigated due to its excellent performance in electrocatalysts, photocatalysts, supercapacitors and secondary batteries. However, there are only a few fabrication methods to synthesize stable 1T MoS2 . In this work, exfoliated MoS2 is employed as seed crystals for the nucleation and growth of a stable 1T MoS2 grains by an epitaxial growth strategy. The 1T MoS2 displays a large interlayer spacing around 0.95 nm, excellent hydrophilia and more electrochemically active sites along the basal plane, which contribute an efficient ion/electron transport pathway and structural stability. When employed as the anode material for sodium ion batteries, the 1T MoS2 electrodes can survive 500 full charge/discharge cycles with a minimum capacity loss of 0.40 mAh g −1 cycle −1 tested at a current density of 1.0 A g −1, and the capacity degradation is as low as 0.39 mAh g −1 cycle −1 at a current density of 2.0 A g −1 .